Long-term outcomes with frontline nilotinib versus imatinib in newly diagnosed chronic myeloid leukemia in chronic phase: ENESTnd 10-year analysis - Kantarjian, Hagop M. (Leukemia, 2021)
In the ENESTnd study, with ≥10 years follow-up in patients with newly diagnosed chronic myeloid leukemia (CML) in chronic phase, nilotinib demonstrated higher cumulative molecular response rates, lower rates of disease progression and CML-related death, and increased eligibility for treatment-free remission (TFR). Cumulative 10-year rates of MMR and MR(4.5) were higher with nilotinib (300 mg twice daily [BID], 77.7% and 61.0%, respectively; 400 mg BID, 79.7% and 61.2%, respectively) than with imatinib (400 mg once daily [QD], 62.5% and 39.2%, respectively). Cumulative rates of TFR eligibility at 10 years were higher with nilotinib (300 mg BID, 48.6%; 400 mg BID, 47.3%) vs imatinib (29.7%). Estimated 10-year overall survival rates in nilotinib and imatinib arms were 87.6%, 90.3%, and 88.3%, respectively. Overall frequency of adverse events was similar with nilotinib and imatinib. By 10 years, higher cumulative rates of cardiovascular events were reported with nilotinib (300 mg BID, 16.5%; 400 mg BID, 23.5%) vs imatinib (3.6%), including in Framingham low-risk patients. Overall efficacy and safety results support the use of nilotinib 300 mg BID as frontline therapy for optimal long-term outcomes, especially in patients aiming for TFR. The benefit-risk profile in context of individual treatment goals should be carefully assessed.